CFD in Sport - a retrospective; 1992 - 2012 - Hanna, R. K. (Procedia Engineering, 2012)
Since commercial Computational Fluid Dynamics, CFD, was first used in anger within sport in the early 1990s it has now evolved to become a dominant, if not indispensible, sports equipment design technology that can produce legal competitive advantage improvements and performance enhancement in elite sport - in effect it can be a killer engineering "app" in sport. This paper will trace the origins of CFD in Motor Sport, Americas Cup Yachting and various Olympic Sports up to its ubiquitous utilization today where it can yield near real-time fluid flow simulation predictions and virtual product development. Indeed, CFD has had a significant impact in the last 20 years on the design of sports stadia, various winter & summer sports equipment design, understanding of ball sports, all motor sport categories, world speed record attempts, numerous water sport equipment designs and various flying related sports activities. A comparison of CFD in sport capabilities between 1992 and 2012 will be offered in this paper and the underlying enabling technology trends described that have helped to make this transformation possible. Finally, the author offers future trend predictions for CFD (and associated multiphysics) technologies in sport for the next 20 years; such as virtual athletes, biomedical applications, enhanced training scenarios, on-the-day-of-the-race climate and landscape modeling, new materials and their fluid-structure effects, video & web based CFD solutions, and the increasing overlap of electronics and mechanics in sports engineering. Indeed, the cross fertilization of technologies from Hollywood movies, mobile phones, the internet and video games to CFD in sports engineering remains to be fully exploited.